Application of International Accounting Standard No (ias26) (Accounting and reporting for retirement benefit plans) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The aim of this research to study the application of IAS (26) (accounting and reporting on retirement benefit plans) through the defined contribution plan amended in accordance with the salaries of state and public sector employees Law No. 22 of 2008 "amended" and the unified Pension Law No. 9 of 2014 "amended" In accordance with the unified accounting system in the State Employees Pension Fund in Baghdad, the importance of the research lies in light of its presentation of intellectual, knowledge and applied contributions through this application and represented the research community of pension funds located in Iraq represented by the research sample (State Employees Pension Fund in Baghdad ) and the research adopted the fiscal year ending in 2015 represented by the financial statements for that year being the last financial statements issued as the year of the beginning of the application and the problem of the research was the non-application of the IAS (26)  (accounting and reporting of Pension Benefit Plans) - the defined contribution plan was amended in accordance with the law on salaries of state and public sector employees No. 22 of 2008 "amended" and the unified Pension Law No. 9 of 2014 "amended"" In accordance with the unified accounting system in the State Employees Pension Fund. One of The most important conclusions reached by the research is based on this application of International Accounting Standard No. (26) (Accounting and Report on Retirement Benefit Plans) - Specific Contributions Plan amended in accordance with the Salaries of State and Public Sector Employees Law No. (22) of 2008 "amended" and the Unified Retirement Law No. (9) of 2014 "amended" in line with the unified accounting system in the State Employees Pension Fund in Baghdad The employee's retirement salary will be calculated since the start of his job service and not as currently in force when Referred him to retirement based on the provisions of the Unified Retirement Law No. (9) of 2014 "amended". The main recommendation of this research is the adoption of this application of the IAS (26) (accounting and reporting of Pension Benefit Plans) amended in accordance with the law on salaries of state and public sector employees No. 22 of 2008 "amended" and the unified Pension Law No. 9 of 2014 "amended"" In accordance with the unified accounting system in the State Employees Pension Fund in Baghdad, where the employee's retirement benefit obligations (salaries) are calculated from the beginning of the employee in his job service until his referral to retirement.